The Role of Job Satisfaction in Mediating the Effects of Self-Efficacy and Perceived Organizational Support on Work Engagement at the Ministry of Religious Affairs of the Republic of Indonesia - Adri Dinizulfa; Corry Yohana; Christian Wiradendi Wolor (International Journal Labs, 2026)
Employee work engagement has become a crucial factor in improving organizational effectiveness, particularly in public sector institutions facing increasing demands for accountability, service quality, and bureaucratic transformation. Variations in individual performance consistency and employee competency levels indicate the need to understand the psychological and organizational factors influencing employee engagement. This study aims to examine the effects of self-efficacy and perceived organizational support on work engagement, with job satisfaction as a mediating variable among employees of the Directorate General of Islamic Education, Ministry of Religious Affairs of the Republic of Indonesia. This research employed a quantitative approach using an explanatory research design. Data were collected through a Likert-scale questionnaire distributed to civil servants, involving 234 respondents selected from a population of 574 employees using a stratified random sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that self-efficacy and perceived organizational support have positive and significant effects on job satisfaction and work engagement. Furthermore, job satisfaction significantly influences work engagement and mediates the relationships between self-efficacy, perceived organizational support, and work engagement through complementary partial mediation. These findings highlight that strengthening employees’ confidence, organizational support systems, and job satisfaction mechanisms are essential strategies for enhancing work engagement in public sector organizations. This study contributes to the human resource management literature by providing empirical evidence from the context of the Indonesian government bureaucracy.